Teologi Pluralis Gerakan Ahmadiyah Indonesia (GAI) Di Yogyakarta - Pratama, M. Guntur Sandi; Ulinnuha, Roma; Putra, Andi Eka (AL-ADYAN, 2024)
The phenomenon of the spirituality movement in the modern world has penetrated into the foundations of society. Modern humans always long for a happy life, so people enter into spiritual activities, one of which is by joining GAI which aims to gain a new spiritual life. GAI's offer of spiritual life makes a person have a pluralist attitude in his life in the social realm. The purpose of this article is to find out about their spiritual activities and how they view other Muslim and non-Muslim communities. The method of this research is field research, which uses a religious phenomenology approach. The results of this research show that GAI have dimensions of spirituality such as allegiance and Qur'anic ethics which enable them to feel inner peace. Apart from that, they also view people from other Muslim communities as Muslims in general, and their attitude towards the Ahl-Kitab does not view them with respect. In GAI's view, there is nothing wrong with a Muslim man marrying a non-Muslim woman and eating food slaughtered by the people of the Bible. The conclusion of this article is that a spiritual life causes GAI's religious understanding to become pluralistic and able to open itself to other views.